B-cell-activating factor in rituximab-treated patients with anti-MAG polyneuropathy. Issue 11 (16th December 2010) - Benedetti, Luana; Zardini, Elisabetta; Briani, Chiara; Beronio, Alessandro; Gastaldi, Stefania; Jarius, Sven; Mancardi, Gian Luigi; Schenone, Angelo; Franciotta, Diego
Abstract : Background: Antimyelin-associated glycoprotein (MAG) polyneuropathy is a slowly progressive distal form of mixed motor-sensory polyneuropathy that is scarcely responsive to conventional immunosuppressive therapy. Rituximab, a B-cell depleting antibody, is a promising therapeutic choice for anti-MAG polyneuropathy, and the evaluation of factors, such as B-cell-activating factor (BAFF), that control B-cell homeostasis is important to understand how this drug works. Methods: Using an ELISA method, the authors measured serum BAFF concentrations in 23 patients with anti-MAG polyneuropathy, before and after rituximab therapy, in 20 neurological controls and in 14 healthy subjects. The patients were followed up over a mean period of 38±12 months and categorised as responders/non-responders, and, between the responders, as relapsing/non-relapsing. Results: Pretherapy serum BAFF concentrations in non-responders were higher than in responders (cut-off 1665 pg/ml; sensitivity 71.4%; specificity 93.7%; likelihood ratio 11.4), with the highest post-therapy increases in responders. In the responders who relapsed, relapses occurred when serum BAFF concentrations returned to baseline values, 1–2 years after blood B-cell reappearance. Conclusions: Before and during therapy, measurements of serum BAFF in rituximab-treated patients with anti-MAG polyneuropathy may help predict the response to the therapy. The findings in this study also provide information about rituximab-induced modifications on B-cell homeostatic regulation.